2006
DOI: 10.1097/01.mpa.0000191645.01926.8f
|View full text |Cite
|
Sign up to set email alerts
|

Local and Systemic Effects of Hypertonic Solution (NaCl 7.5%) in Experimental Acute Pancreatitis

Abstract: The administration of hypertonic saline solution in experimental AP attenuated hemodynamic alterations, decreased inflammatory cytokines, diminished systemic lesions and pancreatic acinar necrosis, prevented pancreatic infection, and reduced the mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 43 publications
3
28
0
3
Order By: Relevance
“…In a previous study we have demonstrated that reduction of IL-6 and IL-10 production by inhibition of PGE 2 , without reduction of TNF-␣ level, did not influence the severity of AP [18] . We have also shown that administration of hypertonic saline solution attenuates the inflammatory response, reduces the hemodynamic alterations, the pancreatic infection and the mortality rate in an experimental model of acute pancreatitis [17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study we have demonstrated that reduction of IL-6 and IL-10 production by inhibition of PGE 2 , without reduction of TNF-␣ level, did not influence the severity of AP [18] . We have also shown that administration of hypertonic saline solution attenuates the inflammatory response, reduces the hemodynamic alterations, the pancreatic infection and the mortality rate in an experimental model of acute pancreatitis [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Injection flow was 0.2 ml/min. Previous studies in our laboratory with this model have shown a mortality rate of 35% after 72 h [17,18] . In the sham group, sodium taurocholate injection was omitted, but the surgical procedure was identical to the other groups, including bile duct cannulation.…”
Section: Induction Of Apmentioning
confidence: 99%
“…3,16 Administration of agents that antagonize or diminish the production of TNF-is associated with decreasing of the systemic effects of acute pancreatitis. 17,18 In a previous study we have showed that treatment of rats with acute pancreatitis by administration of hypertonic saline solution reduces the production of inflammation markers (inducible nitric oxide synthase, cyclooxygenase 2, TNF-, and IL-6) in pancreatic tissue. The volume of ascitic fluid and level of cytokines in ascitic fluid were also reduced, decreasing the systemic inflammatory response in experimental acute pancreatitis.…”
Section: Macrophagesmentioning
confidence: 99%
“…Diversos mediadores antiinflamatórios foram identificados; entre eles destacam-se as interleucinas IL-6 e IL-10 que, 28,42,45,92,93 Trabalhos anteriores realizados no LIM-37 da FMUSP mostraram que a solução salina hipertônica é capaz de reduzir a produção de IL-6 e IL-10 nos animais com pancreatite aguda. 64 Esses dados sugerem que o mecanismo de liberação de IL-6 e IL-10 nas síndromes inflamatórias sistêmicas (pancreatite aguda) seja diferente do mecanismo que ocorre na isquemia/reperfusão hepática, em que existe lesão direta (isquêmica) de importante contingente de macrófagos hepáticos (células de Kupffer).…”
Section: Discussão 58 _______________________________________________unclassified
“…52,53,56,57,63 Adicionalmente, um trabalho recente, realizado no LIM-37 da FMUSP, demonstrou que a administração de solução hipertônica melhora as medidas hemodinâmicas e reduz as citocinas inflamatórias, as lesões sistêmicas, a infecção e a necrose acinar pancreática, resultando na queda significativa da taxa de mortalidade na pancreatite aguda experimental. 64 A presença de alterações hemodinâmicas e a liberação de citocinas inflamatórias, que provocam tanto lesões locais como sistêmicas, sugerem que, no transplante de fígado, a administração de solução salina hipertônica possa ser útil na redução dessas alterações.…”
Section: Introdução 6 _______________________________________________unclassified